Searching for evidence of jet-cloud interaction in radio galaxies : First results for 3C 381 - Reynaldi, María Victoria (2013)
We present results of Gemini spectroscopy and Hubble Space Telescope imaging of the 3C 381 radio galaxy. Possible ionizing mechanisms for the extended emission-line region were studied through state-of-the-art diagnostic analysis employing line ratios. Photoionization from the central engine as well as mixed medium photoionization models fail in reproducing both the strengths and the behaviour of the highest excitation lines, such as [Ne v]λ3424, He ii and [O iii]λ5007, which are measured at very large distances from the active galactic nucleus. Shock-ionization models provide a better fit to the observation. Expanding shocks with velocities higher than 500 km s-1 are capable of reaching the observed intensity ratios for lines with different ionization states and excitation degrees. This model also provides a direct explanation of the mechanical energy input needed to explain the high-velocity line-splitting observed in the velocity field.